Interictal high frequency oscillations correlating with seizure outcome in patients with widespread epileptic networks in tuberous sclerosis complex. Issue 10 (5th September 2014) - Okanishi, Tohru; Akiyama, Tomoyuki; Tanaka, Shin‐Ichi; Mayo, Ellen; Mitsutake, Ayu; Boelman, Cyrus; Go, Cristina; Snead, O. Carter; Drake, James; Rutka, James; Ochi, Ayako; Otsubo, Hiroshi
Summary Objective Multiple tubers in patients with tuberous sclerosis complex (TSC) often are responsible for drug‐resistant epilepsy. The complexity of the epileptic network formed by multiple tubers complicates localization of the epileptogenic zone that is needed to design a surgical treatment strategy. High frequency oscillations (HFOs) on intracranial video‐electroencephalography (IVEEG) may be a valuable surrogate marker for the localization of the epileptogenic zone. The purpose of this study was to test the hypothesis that high occurrence rate (OR) of interictal HFOs can guide the localization of the epileptogenic zone. Methods We analyzed the OR of interictal HFOs at 80–200 Hz (ripples) and >200 Hz (fast ripples, FRs). We divided OR of interictal HFOs between high and low rates by thresholding. We analyzed the correlation between seizure outcomes using Engel classification and the resection ratio of the seizure onset zone (SOZ), and high‐OR HFOs using ordinal logistic regression analysis. Results We collected 10 patients. The seizure outcomes resulted in Engel classification I in three patients, II in four, III in one, and IV in two. High‐OR ripples (5–57 [mean 29] channels, 1–4 [2.8] lobes) and high‐OR FRs (9–66 [mean 27] channels, 1–4 [2.6] lobes) were widely distributed. The resection ratio of SOZ did not show statistically significant correlation with the seizure outcome. The resection ratio of high‐OR ripples showed statistically significant correlation with the seizure outcome (p = 0.038). The resection ratio of high‐OR FRs showed statistically significant correlation with the seizure outcome (p = 0.048). Significance The multiple extensive zones with high‐OR HFOs suggest a complex and widespread epileptic network in patients with TSC. In a subset of TSC patients with drug‐resistant epilepsy, resection of cortex with both interictal high‐OR FRs and ripples on IVEEG correlated with a good seizure outcome.